Fabrication of rGO-CuO and/or Ag2O nanoparticles incorporated polyvinyl acetate based mixed matrix membranes for the removal of Cr6+ from anti-corrosive paint industrial wastewater. Issue 2 (April 2021) - Yaseen, Muhammad; Maria; Farooq, Muhammad Usman; Ahmad, Waqas; Subhan, Fazle
Abstract: Herein we report the fabrication of ternary system mixed matrix membranes based on polyvinyl acetate (PVAc) incorporated reduced graphene oxide (rGO) and CuO or Ag2 O nanoparticles as filler in different weight ratios via non-solvent induced phase inversion separation method. The fabricated membranes were characterized for chemical composition porosity, pore distribution, surface roughness, thickness, water contact angle and mechanical strength. Scanning electron microscopy and atomic force microscopy analyses revealed that pure PVAc exhibited smooth and uniform surface while PVAc/rGO/Ag2 O and PVAc/rGO/ACuO membranes possessed rough and uneven topography and higher surface porosity. PVAc/rGO/CuO and PVAc/rGo/Ag2 O membranes exhibited total permeate flux of 1.60 × 10 –2 g/m 2 s and 1.28 × 10 –2 g/m 2 s corresponding to net removal of 99.9% and 98.0% respectively from model wastewater of Cr 6+ under the optimized experimental conditions. Interestingly, under these optimized conditions, PVAc/rGO/CuO membrane achieved Cr 6+ removal of 99.9% from anti-corrosive paint industrial wastewater (as real sample) with a flux of 1.90 × 10 -2 g/m 2 s, which was much higher than many state of the art membranes. The uptake of Cr 6+ from real solution was confirmed by EDX and AFM analysis of the post-separation membrane. The newly designed PVAc/rGO/CuO membrane, attributed to cost-effectiveness, environmental greenness, ease of syntheisis and high efficiency, can be envisioned of potential applications for the remediation of Cr 6+ and other similar pollutants from real industrial wastewater. Graphical Abstract: ga1 Highlights: PVAc/rGO/CuO hybrid membranes were prepared via sonication approach. rGO/CuO NPs resulted in increasing porosity and surface area of hybrid membranes. PVAc/rGO/CuO and PVAc/rGO/Ag2 O MMMs were applied for Cr 6+ removal. PVAc/rGO/CuO showed 99.9% Cr 6+ removal from anti-corrosive paint solution. Cr 6+ removal was confirmed by AFM, SEM-EDX and FTIR analysis.